Apresentação ("Revista Gestión y Conexiones", 2014)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2014.3.1.7853.17-20. Apresenta a Edição Especial: Inovação, Tecnologias Assistivas e Acessibilidade.